KONSEPSI MANAJEMEN MUTU PENDIDIKAN - Rusli Kembaren (JGK (Jurnal Guru Kita), 2022)
Abstract:  Education Quality Management Concept. This journal aims to provide an explanation of the concept of quality, school quality and the quality of educational institutions. This journal also focuses on the quality of education managed by professional institutions through integrated quality management. Educational institutions as producers of the service sector must pay attention to the quality, the quality of the managerial and academic aspects. Both of these aspects can be achieved through the application of the concept of total quality management (TQM). TQM is a management concept that places all university personnel (academics) as individuals who have responsibility for quality in accordance with their duties and functions. Quality of education is the degree of excellence in managing education effectively and efficiently to give birth to academic and extracurricular excellence in students who are declared to have passed for one level of education or completed a certain learning program. National Education Standards aim to ensure the quality of national education in the context of educating the nation's life and shaping the character and civilization of a dignified nation. National Education Standards are refined in a planned, directed, and sustainable manner in accordance with the changing demands of local, national, and global life.  Keywords: Conception of Quality Educational